Loading of the Spine in Low Back Pain Patients Does Not Induce MRI Changes in Modic Lesions: A Prospective Clinical Study - Hanna Hebelka; Helena Brisby; Alfred Erkmar; Kerstin Lagerstrand (Diagnostics, 2022)
Modic changes (MCs) are gaining increased interest as potential generators of low back pain (LBP). The current aim was to investigate possible spinal loading effects on the MRI signal in MCs in patients with LBP. Supine lumbar MRIs were performed and immediately repeated with axial loading in 100 LBP patients. A total of 43 patients (23 male, mean age 45.7 years) had MCs. Each Modic was outlined on all sagittal T2-weighted images (>25% affected vertebrae). For reference, regions of interest were placed in both vertebrae without Modic and in Modic-free tissue in vertebrae with Modic. The Modic signal intensity, normalized to cerebrospinal fluid, and Modic volume were compared between MRIs with and without spinal loading. Of the 94 MCs, 36.2% (n = 34) were type I, 58.5% (n = 55) were type II, and 5.3% (n = 5) were type III. No differences in Modic volume (mean 0.046 cm3; p = 0.25) between the MRIs with and without spinal loading were found. In addition, no significant changes in Modic signal were induced by loading (mean 1.5% difference; p = 0.308). Loading increased the signal in the reference regions of interest in vertebrae both with Modic (mean 5.5%; p = 0.002) and without (mean 3.5%; SD 0.09; p = 0.02). To conclude, MRIs performed with and without spinal loading showed no change in either volume or signal of MCs, suggesting that most MCs are not instantaneously influenced by biomechanical load.